Diagnóstico citopatológico de afecções mamárias em cadelas: revisão - Colodel, Márcia Moleta [UNESP] (2010)
Mammary affection in bitches is a routine finding in small animal clinic. The use cytopathological examination as a means to obtain mammary lesion diagnosis in the last decades in Veterinary Medicine. The advantages of this examination are: it is fast, cheap, effective, simple and little invasive. The mammary samples for cytopathology exam may be obtained from glandular secretion or more commonly via fi ne needle cytology that may be performed with or without aspiration. In order to obtain relevant clinical results, it is important to get good samples and have good knowledge of cell morphology and cell disposition. Despite lowing inconclusive results, the cytopathology allows to distinguish neoplastic lesions from infl ammatory, hyperplasic or degenerative. It can also help in the identifi cation of infectant agents and guide a fast and appropriate therapy. Therefore it can be used to diagnose mammary conditions. The objective of this study is to encourage veterinarians to insert the cytopathology examination in the array of auxiliary tests for mammary lesions in bitches.